1956
DOI: 10.1021/j150538a010
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Vapors by High Polymers

Abstract: Some alternatives to the Flory-Huggins-Guggenheim treatment of sorption of liquids by polymers are examined, using data on three systems, water-collagen, benzene-rubber and toluene-polystyrene. It is found that a simple rigid site type of sorption theory is illuminating for the hydrocarbon systems but breaks down badly when applied to water-collagen mixtures. However, an exact "clustering" theory may be applied to all three of these systems. This theory, which is based on the statistical mechanics of fluctuati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
870
1
12

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 849 publications
(916 citation statements)
references
References 0 publications
33
870
1
12
Order By: Relevance
“…This is consistent with the analysis of water to cellulose sorption curves using the Zimm and Lundberg (1956) cluster model. This model also predicts a large increase in the cluster size near saturation (Starkweather 1975), and it is found that decreases in magnitude as the w 1 / 2 DM yDt mix humidity increases to 97% RH.…”
Section: Resultssupporting
confidence: 90%
“…This is consistent with the analysis of water to cellulose sorption curves using the Zimm and Lundberg (1956) cluster model. This model also predicts a large increase in the cluster size near saturation (Starkweather 1975), and it is found that decreases in magnitude as the w 1 / 2 DM yDt mix humidity increases to 97% RH.…”
Section: Resultssupporting
confidence: 90%
“…The mechanism responsible for termination of short chains is less well-understood than for long chains, but has been compared with center-of-mass diffusion where it is expected that a S should equal 0.50-0.66 according to Zimm's treatment 69 of the Stokes-Einstein equation. 70 This postulate is consistent with the results for PSTY, PVAc, and PMMA, but does not agree with the high value of 0.78 determined for PMA.…”
Section: Termination In Dilute Solutionmentioning
confidence: 99%
“…Let us now examine the second hypothesis. The isotherm shape can be then analyzed with the ZimmeLundberg theory [11]. These authors define a clustering function f ZL defined by Clusters are present when f ZL > À1.…”
Section: Resultsmentioning
confidence: 99%